Chronic Calcified Subdural Hematoma: Case Report and Review of the Literature - Pappamikail, L (2013)
Background: Calcified chronic subdural hematoma is a rare but known entity, estimated to represent 0.3-2.7% of chronic subdural hematomas. Although surgical treatment is unanimous for chronic subdural hematomas, therein lies some doubt on it being applied to calcified chronic subdural hematomas. Case Description: We report a case of a 73‑year‑old male, presenting with deterioration of motor function in his right limbs since 18 months, with computed tomography (CT) scans and magnetic resonance imaging (MRI) documenting a large subdural collection of the left hemisphere, with calcified inner membrane, which was successfully and completely removed, with progressive clinical and radiological improvement. Conclusions: We report a case where this type of rare lesion was removed with a progressive and complete resolution of the patient’s symptoms, restoring his previous neurological condition. From the cases described in the literature and our own experience with this case, we think surgical treatment in these patients, when symptomatic, is necessary and viable, frequently resulting in the patient’s improvement.